PENGARUH PEMBERIANSARI KUNYIT (Curcuma longa L)DAN TEMULAWAK (Curcumaxanthorrhiza Roxb) DALAM AIR MINUM TERHADAP PERFORMA PUYUH JANTAN - Mubarak Akbar; Mohamad Eko Hari P (Jurnal Ilmiah Fillia Cendekia, 2017)
Research about "The Effect of turmeric (Curcuma longa L) and temulawak (Curcuma xanthorrhiza Roxb)juice supplemented in drinking water on quailmale performance" was conducted on May 24 until 27 April 2017 in Duwet Vilage, Wates District, Kediri Regency.The purpose of this research was to know the effect of turmeric (Curcuma longa L) and temulawak (Curcuma xanthorrhiza Roxb)juice in drinking water to the performance of quail male The experiment method assigned to Factorial Randomized Design Complete consisting of 6 treatment combinations and 3 replications. Turmeric and temulawak juice into drinking water as a supplement: Turmeric juice (S1) and temulawak juice (S2) with 3 kinds of dosage of dose 2.5 ml (D1), dose 3,5 ml (D2) and dose 4, 5 ml (D3). The Parameters observed in this study drinking water consumption, feed consumption, body weight gain and feed conversion. Based on the result of the research, it can be concluded that the application of saffron juice (Curcuma longa L) and temulawak (Curcuma xanthorrhiza Roxb) to drinking water to the performance of quailmale, showed good effect on temulawak juice alone, which includes drinking water consumption and feed conversion, Feed intake and body weight gain, whereas at the dose of good effect on dose of 2.5ml, although the statistical analysis has no effect and on the treatment combination there is no significant difference to the performance of the male quail. The provision of saffron juice (Curcuma longa L) and temulawak (Curcuma xanthorrhiza Roxb) is recommended to provide temulawak juice supplement with dose of 2.5ml every 1 liter to give the best result to quail performance as it can improve (FCR) Feed Converation Ratio, and should be done research Go about giving turmeric juice and temulawak with level> 4.5ml every 1 liter water